Tess data for asteroseismology: Timing verification - Essen, Carolina von (2020)
The Transiting Exoplanet Survey Satellite (TESS) is NASA´s latest space telescope dedicated to the discovery of transiting exoplanets around nearby stars. Besides the main goal of the mission, asteroseismology is an important secondary goal and very relevant for the high-quality time series that TESS will make during its two-year all-sky survey. Using TESS for asteroseismology introduces strong timing requirements, especially for coherent oscillators. Although the internal clock on board TESS is precise in its own time, it might have a constant drift. Thus, it will need calibration, or else offsets might inadvertently be introduced. Here, we present simultaneous ground- and space-based observations of primary eclipses of several binary systems in the Southern ecliptic hemisphere, used to verify the reliability of the TESS timestamps. From 12 contemporaneous TESS/ground observations, we determined a time offset equal to 5.8 ± 2.5 s, in the sense that the barycentric time measured by TESS is ahead of real time. The offset is consistent with zero at the 2.3σ level. In addition, we used 405 individually measured mid-eclipse times of 26 eclipsing binary stars observed solely by TESS in order to test the existence of a potential drift with a monotonic growth (or decay) affecting the observations of all stars. We find a drift corresponding to σ drift = 0.009 ± 0.015 s day-1. We find that the measured offset is of a size that will not become an issue for comparing ground-based and space data for coherent oscillations for most of the targets observed with TESS.